1993
DOI: 10.1159/000118966
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Calcium Ions to the Generation of Epileptic Activity and Antiepileptic Calcium Antagonism

Abstract: With epileptic activity, neurons show paroxysmal depolarization shifts (PDSs) corresponding to epileptic field potentials (EFPs) generated by the neuronal population. Experimental results indicate that calcium and calcium-dependent currents participate in the generation of these events. Consequently neuronal PDS/EFP were depressed by organic calcium channel blockers. This justifies the hope that calcium channel blockers might be useful in the treatment of human epilepsies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…Thus the other possible explanation for the anticonvulsant action of fluoxetine may be related to its inhibitory effect on ionic channels. Several reports indicated that altered activity of voltage-gated Na + and Ca 2+ channels was involved in the enhancement of neuronal discharges during epilepsy (51)(52)(53), and conventional anticonvulsant drugs were found to block voltage-dependent Na + and Ca 2+ channels (11,13,14,53). Our previous results demonstrating that fluoxetine was a considerably more potent inhibitor of Ca 2+ than Na + channels support the possibility that inhibition of Ca 2+ channels by fluoxetine may contribute to its anticonvulsant action (10).…”
Section: Discussionmentioning
confidence: 59%
“…Thus the other possible explanation for the anticonvulsant action of fluoxetine may be related to its inhibitory effect on ionic channels. Several reports indicated that altered activity of voltage-gated Na + and Ca 2+ channels was involved in the enhancement of neuronal discharges during epilepsy (51)(52)(53), and conventional anticonvulsant drugs were found to block voltage-dependent Na + and Ca 2+ channels (11,13,14,53). Our previous results demonstrating that fluoxetine was a considerably more potent inhibitor of Ca 2+ than Na + channels support the possibility that inhibition of Ca 2+ channels by fluoxetine may contribute to its anticonvulsant action (10).…”
Section: Discussionmentioning
confidence: 59%
“…This, however, could have been expected for verapamil, since voltage-operated Ca 2ϩ channels have been suggested as a pharmacotherapeutic drug target to correct the aberrant pathophysiology of epileptogenesis via a phenomenon known as "intrinsic burst firing" driven by an inward Ca 2ϩ current (Kulak et al, 2004). Several Ca 2ϩ channel antagonists were shown to possess anticonvulsant potential in experimental and clinical studies (De Sarro et al, 1988;Czuczwar et al, 1990;Larkin et al, 1992;Speckmann et al, 1993;Gasior et al, 1995Gasior et al, , 1996Swiader et al, 2002). However, systemic isradipine and verapamil administration per se or in combination with AEDs failed to display any anticonvulsant activity (Czuczwar et al, 1990;Borowicz et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Calcium ions (Ca2+), ubiquitous second messengers in vertebrate cells, are involved in the pathology of epileptic seizures (Speckmann et al, 1993). This assumption is supported by the findings that burst firing of neurons (the best electrophysiological manifestation of seizures) may be triggered by a large influx of Ca 2+ (Schwartzkroin and Wyler, 1980).…”
Section: Introductionmentioning
confidence: 95%